DETERMINAN PERTUMBUHAN LABA PADA PERUSAHAAN SEKTOR HEALTH CARE YANG TERDAFTAR DI BEI PERIODE 2019 – 2022 - Nurani, Bulan Karima; Rahmatika, Ulya; Jayanti, Fitri Dwi (Dinamika Akuntansi Keuangan dan Perbankan, 2024)
The first time the pandemic hit, it impacted the unstable economic crisis in various communities in all world countries. In contrast in the healthcare sector companies can survive due to the soaring demand for drug production and health services. Thus providing an opportunity to get high income in the future, and can even provide an opportunity to get high profits. So in the research period span, it has an impact on increasing or decreasing profits with a high difference. This study was conducted to determine the effect of debt-to-equity ratio, net profit margin, total asset turnover, and current ratio on profit growth in healthcare sector companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The number of companies sampled in this study was 19 companies with data for each of the 4 periods studied with a total of n = 76. This study uses secondary data and this study uses quantitative data types. The analysis method used is multiple linear regression analysis. The results of this study indicate that partially the debt to equity ratio has a negative and significant effect on profit growth, total asset turnover has a positive and significant effect on profit growth, net profit margin and current ratio have a negative and insignificant effect on profit growth.